Britain's economic blockade of Germany, 1914-1919 - Osborne, Eric W. (Cass series--naval policy and history ;, 2004)
Great Britain's economic blockade of Germany in World War I was one of the key elements to the victory of the Entente. Though Britain had been the leading exponent of blockades for two centuries, the World War I blockade was not effective at the outbreak of hostilities. Pre-war changes had led to the Admiralty supplanting the Royal Navy's leadership role in favour of direction from the civilian branch of government on the basis of international law. The struggle between the primacy of international law and military expediency lasted for nearly two years, as the British tried to reconcile the.